Genetics, paleontology, and macroevolution - Levinton, Jeffrey S. (Cambridge University Press, 2001)
An engaging area of biology for more than a century, the study of macroevolution continues to offer profound insight into our understanding of the tempo of evolution and of the evolution of biological diversity. What regulates biological diversity and its historical development? Can it be explained by natural selection alone? Has geologic history regulated the tempo of diversification? This expanded and updated second edition offers a comprehensive look at macroevolution and its underpinnings, with a primary emphasis on animal evolution. From a Neodarwinian point of view, it integrates evolutionary processes at all levels to explain the diversity of animal life. It examines a wide range of topics including genetics and speciation, development and evolution, the constructional and functional aspects of form, fossil lineages, and systematics, and it takes a hard look at the Cambrian explosion. Researchers and graduate students will find this book a most comprehensive examination of macroevolution
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Paläontologie; Macroevolution; Genetics; Paleontology; Entwicklungsbiologie; Makroevolution; Evolution; Phylogenie; Genetik